2014
DOI: 10.5014/ajot.2015.013532
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of Occupational Therapy Level II Fieldwork Students: Impact on and Predictors of Clinician Productivity

Abstract: This study aimed to determine whether a difference in productivity exists between clinicians supervising and not supervising a Level II occupational therapy student and whether factors including clinician years of experience, practice setting, and clinician productivity without a student could predict clinician productivity while supervising a student. We used paired-sample t tests to examine clinician productivity with and without a student in 109 clinician-student encounters and regression analysis to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…In addition, as outlined in the literature, this study reveals there were a number of opportunities particularly in relation to student learning through problem‐based and peer learning approaches, which provided mutual support between students and, with time, less dependency on supervisors in some cases (Aiken et al ., ; Baldry Currens & Bithell, ; Blakely et al ., ; Daniels, ; Flood et al ., ; Gallagher & Cahill, ; Martin & Edwards, ; Martin et al ., ). Ozelie, Janow, Kreutz, Mulry and Penkala () report that clinical years of experience, practice area and productivity without a student are predictors for therapist productivity while supervising a student. Although their study did not explore the challenges of 2:1 placement models, therapists who were in acute health practice areas and had longer clinical experience reported that their productivity was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as outlined in the literature, this study reveals there were a number of opportunities particularly in relation to student learning through problem‐based and peer learning approaches, which provided mutual support between students and, with time, less dependency on supervisors in some cases (Aiken et al ., ; Baldry Currens & Bithell, ; Blakely et al ., ; Daniels, ; Flood et al ., ; Gallagher & Cahill, ; Martin & Edwards, ; Martin et al ., ). Ozelie, Janow, Kreutz, Mulry and Penkala () report that clinical years of experience, practice area and productivity without a student are predictors for therapist productivity while supervising a student. Although their study did not explore the challenges of 2:1 placement models, therapists who were in acute health practice areas and had longer clinical experience reported that their productivity was not affected.…”
Section: Discussionmentioning
confidence: 99%
“…, Ozelie et al . ). These studies have provided useful contributions, though each has had its limitations related to small sample sizes or low response rates; narrowly defined definitions of productivity which have failed to account for 100% of CE and student time; and/or problematic treatment of CE–student team data which has not taken into consideration the time that CEs and students may have spent engaged in joint working.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of benefits for student learning, much has been written about the pairedplacement model (Baldry Currens and Bithell 2003, DeClute and Ladyshewsky 1993, O'Connor et al 2012, Dawes and Lambert 2010, Briffa and Porter 2013. In the case of the latter, there is much still to learn (Rodger et al 2011, Ozelie et al 2015, Sevenhuysen et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulty articulating professional reasoning from theory to practice is reported among occupational therapists in the literature (Kinn & Aas, 2009) and may contribute to a perception by students that a disconnect exists between the classroom and practice (Elliot, Velde, & Wittman, 2002;Towns & Ashby, 2014). Additional barriers to fieldwork educators' ability to provide quality supervision include large caseloads, limited resources, and high standards for productivity (Ozelie, Janow, Kreutz, Mulry, & Penkala, 2015). An increased understanding of the components of quality fieldwork education may enhance student learning and professional socialization.…”
mentioning
confidence: 99%